2013
DOI: 10.1186/1471-2253-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing physical functional status in intensive care unit survivors two years after discharge

Abstract: BackgroundStudies suggest that in patients admitted to intensive care units (ICU), physical functional status (PFS) improves over time, but does not return to the same level as before ICU admission. The goal of this study was to assess physical functional status two years after discharge from an ICU and to determine factors influencing physical status in this population.MethodsThe study reviewed all patients admitted to two non-trauma ICUs during a one-year period and included patients with age ≥ 18 yrs, ICU s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
1
29
0
2
Order By: Relevance
“…The authors reported that raters had been previously trained on the use of the scale, but they did not describe how the scale is used. The results demonstrated a reduction in patients' ability to perform activities of daily living, even 24 months after ICU discharge (16).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The authors reported that raters had been previously trained on the use of the scale, but they did not describe how the scale is used. The results demonstrated a reduction in patients' ability to perform activities of daily living, even 24 months after ICU discharge (16).…”
Section: Discussionmentioning
confidence: 93%
“…According to the results of this review, the Karnofsky/Performance Status Scale Scores is the most widely used tool among researchers in Brazil (15,16,17,18). It has been largely used to assess functional status in patients with incapacitating chronic disease, such as critically ill ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations